Plano de conservação e preservação dos documentos sonoros e audiovisuais da Orquestra Sinfônica da Universidade Federal de Santa Maria - Jost, Betina (2020)
This study presents information, memory and heritage as the keywords of contemporary consciousness. Heritage is a dimension of memory and society needs memory as a source of history, which can be achieved through information. The preservation of information and the different formats where it is registered is the focus of this master's thesis, resulting in a booklet that proposes a plan for the conservation and preservation of sound and audiovisual documents of the Symphonic Orchestra of the Federal University of Santa Maria. The study of sound and audiovisual documents is explored from an archival approach, resulting in a booklet as a product, which is a textbook with an easy-to-understand language, and which brings useful information from a preservation and conservation plan. sound and audiovisual documents. This booklet identifies the formats of the sound and audiovisual materials that must be preserved by the UFSM Orchestra, as well as the methods of preserving and preserving the materials and information, so that access to their content is available as long as possible, regardless where the information is recorded. Equally adequate means of security are identified for the internal environment of the building and the furniture where the documents are located. This is a bibliographic search and practical application. It presents characteristics of a case study, as it is used the means of direct observation, from the different materials that contain information that are investigated to describe the context of documentary production. The booklet provides technical guidance through simple language regarding the technological media used to record sound and audiovisual information, as well as the entire context of the building's internal environment, such as degradation caused by air, temperature, relative humidity, due to incorrect handling and the absence of specific care regarding the forms of storage and packaging. As the media that are part of this institution's Symphony Orchestra, VHS videotapes, CDs and DVDs, need special care, a preservation and conservation plan should contribute to increasing the life expectancy of these formats, so as not to technological obsolescence and also to the environment where the documents are stored. Even more necessary is to preserve the documents of memory of the Symphony Orchestra, as it is a legacy that is made of the past and present for the future, as an extension of its life and as cultural heritage.